The problem of Metaphysics From The Staged Progression To The Final Development - ماشي نور; جلال بدلة (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This article aims to clarify the term metaphysics for Kant and Hegel, as it is an original research from the investigations of German philosophy in general, and critical idealism in particular, so metaphysics was the means that helps man to reach a higher degree of knowledge as it is the philosophical research that is concerned with the search for the nature of things. The German philosopher Kant is credited with establishing the term metaphysics, so that Hegel came to complete his career in his attempt to develop metaphysics, and make it a purely rational science, and enter into all mental, religious, and historical fields. In his philosophy, Kant emphasized rational and empirical knowledge, and used the mind in order to find a scientific metaphysics instead of the traditional one. His books "Critique of Pure Reason" and "Critique of Practical Reason", and with this criticism he wanted to present a tool or means to eliminate the errors that hindered metaphysics from progress; Its reform, then, was the ultimate goal of Kant’s philosophy. The critical approach that Kant followed has had a great impact on philosophy to this day. Hegel’s metaphysics has an important place in his philosophical system as a rational science. He saw that Western metaphysics until the days of Kant failed to reach its perfection, and some had stopped at the reasons for the sterility of metaphysics compared to science. Hegel worked to establish an original metaphysics that transcends the previous doctrines, and deals with its ideas according to The dialectical logic that accommodates the various previous philosophical doctrines, which achieves, from Hegel’s perspective, the completeness of metaphysics.